Does valence of product review matter?: The mediating role of self-effect and third-person effect in sharing YouTube word-of-mouth (vWOM). Issue 1 (11th March 2019) - Bi, Nicky Chang; Zhang, Ruonan; Ha, Louisa
Abstract : Purpose: As YouTubers began to create videos about their personal experience of using products, these video testimonials have become a powerful form of electronic word-of-mouth (eWOM). This study aims to investigate the mediating role of self-effect and third-person effect in the relationships between eWOM seeking and passing along YouTube product review videos (video-based eWOM – vWOM) as a specific form of eWOM. Design/methodology/approach: The paper used a survey to interview a total of 282 respondents at a public university in the Midwest USA with about 18, 000 students. Findings: The results show that perceived third-person effect leads to sharing more positive vWOM, while perceived self-effect results in a high likelihood of passing along negative vWOM. The general eWOM consumption does not have a direct effect on the sharing of vWOM. In addition, the YouTube sharing habit contributes to sharing vWOM regardless of valence. Practical implications: The results provide marketers' insights on how to utilize the social media such as YouTube to improve the visibility of promotional brand messages. Sharing of positive vWOM is due to perceived third-person effect (presumed influence), but sharing negative vWOM is due to perceived self-effect. It also suggests marketers take immediate remedial measures to avoid spreading of negative reviews to other users because if viewers are persuaded to think it could happen to themselves as well, they will spread the video. Originality/value: The paper has theoretical implications. It contributes to the third-person effect and presumed influence literature by exploring its role in spreading the word for products. It also fills the gap in effects of eWOM literature by examining the mediating role of the valence of video-based eWOM in the spread of eWOM.